Research on the Integration and Development of Digital Economy and Real Economy - Huang, Heng (Transactions on Economics, Business and Management Research, 2023)
This article examines the fusion and advancement of the digital economy and the tangible economy by juxtaposing theoretical frameworks with practical applications. To begin with, this article aims to elucidate the concept and interplay between the virtual economy and the tangible economy, while examining the ramifications of the virtual economy on the tangible economy and vice versa. Furthermore, an analysis is conducted on various contributing factors such as technological advancements, economic conditions, policy frameworks, and societal interactions that influence the amalgamation and progress of the virtual and tangible economies. Additionally, the article delves into the pathways for integrated development between the virtual and tangible economies. These pathways encompass areas such as policy support and innovation initiatives, technological enhancements and industrial metamorphosis, talent cultivation and market requirements, infrastructure development and resource sharing, among others. Ultimately, policy recommendations are proposed in order to facilitate the harmonious development of the virtual economy and the tangible economy. These recommendations aim to offer theoretical guidelines and practical insights for the integrated development of China’s virtual economy and tangible economy.